EFEKTIVITAS MODEL PEMBELAJARAN OPEN ENDED DENGAN MEDIA POWER POIN PADA MATERI LINGKARAN DAN BANGUN RUANG KUBUS DAN BALOK - Suminto (Universitas Muhammadiyah Pringsewu, 2016)
The students' math achievement in the second grade of the SMP Negeri 3 Pringsewu is not effective, even though, in learning process, the teacher has involved the students actively and give broad chance to students to gain more knowledge. From those condition, alternative learning is needed by using the open ended learning model with the power point presentation. This research used descriptive research. Researcher used observation sheet they were teacher's ability sheet, activity's student sheet, respond's student sheet, then to get students' learning achievement were used essay. Based on the data analysis of open ended learning process with power point presentation toward the subject of circle, square, and rectangle. It can be concluded that the result was effective. It can be seen in the teacher's ability was 83%, students' activity was 77,4%, students' response was 84,2% and the number of the students achieves the effective learning about 79,48%. Keywods: open ended learning model, effectiveness in learning